Pengaruh Promosi Dan Persepsi Harga Terhadap Keputusan Pembelian Toko Sajodo Snack - Rahman, Resilva Amalia; Lestari, Suci Putri; Asyiah, Ai Kusmiati (Jurnal Bisnis, Manajemen dan Akuntansi, 2024)
This research aims to determine the influence of promotion and price perception simultaneously on purchasing decisions Sajodo Snack Shop. The partial of promotion and price perception on purchasing decisions at Sajodo Snack Shop. The method used in this research is causal descriptive with a quantitative approach. With a research sample of 100 people as respondents from Sajodo Snack Shop consumers. The data used is primary data. The analytical tool used in this research is multiple linear regression using the SPSS version 25 application. The results of simultaneous testing of promotion and price perception have a significant effect on purchasing decisions. Partially, the promotion variable has a significant effect on purchasing decisions, as well as the price perception variable partially has a significant effect on purchasing decisions.